Case report: A case of sepsis caused by rickettsial infection-induced hemophagocytic syndrome - Cao, Yanli; Liu, Peijun; Song, Qiuling; Wang, Jing (Frontiers in Medicine, 2023)
Hemophagocytic lymphohistiocytosis (HLH) is a rare histiocytic disorder characterized by reactive hyperplasia of the mononuclear phagocytic system, which is primarily caused by dysfunction of cytotoxic killer cells and natural killer cells leading to antigen clearance barriers, and the overactivation of the mononuclear phagocytic system due to continuous antigen stimulation. HLH encompasses a group of clinical syndromes marked by the overproduction of inflammatory cytokines-a 68-year-old Chinese man presented with persistent fever, chills, nausea, and vomiting. The patient had no history of any underlying conditions. Laboratory investigations revealed decreased levels of red blood cells, white blood cells, and platelets, along with reduced natural killer cell activity, increased CD25, hyperferritinemia, and the detection of Rickettsia DNA in his blood, meeting the diagnostic criteria of the Histiocyte Society HLH-2004 guidelines. The patient was treated with antibiotics, improving anemia, glucocorticoid therapy, and continuous renal replacement therapy (CRRT), temporarily improving his condition. However, the patient died two years later from chronic renal failure caused by septic shock.